A polifarmácia de medicamentos psicotrópicos na atenção primária à saúde do município de Maracanaú - Correia, Gabriela de Almeida Ricarte (2019)
The research Polypharmacy in the use of psychotropic drugs in Primary Health Care aimed to characterize the polypharmacy of psychotropic drugs in users of Primary Health Care who receive their drugs in the Pharmacy Pole of Maracanaú-Ce. This was a cross-sectional study using a quantitative approach. Data were collected by the principal researcher through a structured questionnaire and consultation with medical prescriptions. A total of 293 APS users were interviewed seeking medication receipt at the Pharmacy Pole. The results showed that most users were female (70.65%), the average age of 48.94 years and not receiving social benefits (66.55%). They have elementary school level (56.99%) and married marital status (49.83%). Most users had no psychiatric hospitalization in the last 12 months and the main secondary disease was hypertension (46.15%). APS users predominantly perform the medication approach (82.59%) and a small part perform the non-medication approach in an associated manner (17.41%), mainly individually (88.23%) by the professional psychologist (76 , 47%) being followed in other places, where CAPS was the most sought (75.20%). Considering psychotropic polypharmacy as the use of two or more drugs for the same patient, it was found that 44.70% of users practice polypharmacy, where the most consumed drugs were: amitriptyline, diazepam, fluoxetine, risperidone, carbamazepine, paroxetine, alprazolam , clonazepam, sodium valproate and levomepromazine. The main indications for medication use were: nervousness (42.10%), insomnia (31.1%) and depression (13.15%) and the main problems resulting from this use were: drowsiness (27.27%) and dizziness (18.18%). Users report that they no longer receive the drugs in this pharmacy (37.20%) and when this occurs, buy (98.17%). Regarding the origin of the prescription, most are from the Basic Health Unit (69.62%), prescribed by the clinician (79.52%). The factors associated with psychotropic polypharmacy were: gender, age, education, marital status, health problem, hypertension, psychiatric hospitalization, followup in other places, origin of the prescription, specialty of the prescriber and no longer receiving the drugs in this pharmacy. After logistic regression analysis by the bacward model, the factors that were associated with psychotropic polypharmacy were: origin of prescription and follow-up in other places. The study revealed that most APS users practice polypharmacy of psychotropic drugs and that non-drug approaches are still underused in health services, suggesting that mental health care practices are implemented in these services in geographically known territory.